Implementation Learning Science for Supporting The Development of Critical Rationale In Early Childhood - Wildan Fauzi Mubarock; Nancy Angelia Purba; Armi Yuneti; Vando Sidauruk; Simon Panjiatan (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
The purpose of this research is to support the maximum development of critical reasoning through real learning experiences in science activities. The research method used in this research is classroom action research which is carried out collaboratively between the research and the classroom teacher. While the subject is the students of group B1 kindergarten State Pembina Kandis totaling 17 children. Data collection techniques through observasion, and documentation. The data analysis technique used descriptive qualitative. The result of this study are based on data generated from the percentage of children’s critical thinking abilities starting pre-cycle by 50%. In the pre-cycle,children’s critical thinking skills are in the Beginning to Develop (MB) category. In the first cycle, the critical thinking ability of the achievement develops according to expectations (BSH), in the second cycle the achievement of the critical thinking ability to think starting from the pre-cycle, cycle 1, cycle II